2020
DOI: 10.1016/j.desal.2019.114170
|View full text |Cite
|
Sign up to set email alerts
|

Experimental testing of aluminium fumarate MOF for adsorption desalination

Abstract: Many researchers consider adsorption systems as a solution for global problems such as global warming and water scarcity. The experimental and numerical data available in literature are basically focusing on using conventional adsorbent materials such as silica gel and zeolites. Recently, metal-organic framework (MOF) materials has been proposed to substitute these conventional adsorbents. Nevertheless, the potential of MOFs has been only numerically investigated without any experimental data from a real syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…A recent study of the same team with a two-bed system confirmed that Al-fumarate outperformed both silica and CPO-27(Ni) depending on the operation temperatures and the operation mode (pure desalination or cogeneration). 395 The water (SDWP up to 14 m 3 /(tonne MOF day)) has a high distilled water quality, is produced at a low thermal and electricity consumption, and at the lowest cost (0.3 $/m 3 ) in comparison with other standard operations (reversed osmosis, multieffect distillation, and multistage flash). 395 The reported AD productivities are an order of magnitude large than in water harvesting.…”
Section: Applications and Performance Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of the same team with a two-bed system confirmed that Al-fumarate outperformed both silica and CPO-27(Ni) depending on the operation temperatures and the operation mode (pure desalination or cogeneration). 395 The water (SDWP up to 14 m 3 /(tonne MOF day)) has a high distilled water quality, is produced at a low thermal and electricity consumption, and at the lowest cost (0.3 $/m 3 ) in comparison with other standard operations (reversed osmosis, multieffect distillation, and multistage flash). 395 The reported AD productivities are an order of magnitude large than in water harvesting.…”
Section: Applications and Performance Assessmentmentioning
confidence: 99%
“… 395 The water (SDWP up to 14 m 3 /(tonne MOF day)) has a high distilled water quality, is produced at a low thermal and electricity consumption, and at the lowest cost (0.3 $/m 3 ) in comparison with other standard operations (reversed osmosis, multieffect distillation, and multistage flash). 395 The reported AD productivities are an order of magnitude large than in water harvesting. Apart from the technology development level, this is importantly due to the wider range of humidities in AD.…”
Section: Applications and Performance Assessmentmentioning
confidence: 99%
“…In this regard, various MOFs such as UiO-66 [61], CPO-27Ni [62], aluminum fumarate [63], and MIL-101(Cr) [64] have been probed in experimental studies as appropriate desalination membranes. However, exploring MOFs as RO membranes using theoretical methods such as molecular dynamics is a very recent development, and the number of articles on this subject is almost limited.…”
Section: Mofs For Water Desalinationmentioning
confidence: 99%
“…One challenge in material selection is the working capacity from the material's equilibrium curves that can be achieved at 40 ∘ C. Most novel materials that have been proposed for adsorption desalination showing high water capacities require regeneration temperatures well above 40 ∘ C, for example, MOF materials (90 ∘ C) 79,80 or zeolites AQSOA Z01 and Z02 (60 ∘ C and 80 ∘ C) 76,77 . Ionogels show outstanding performances at regeneration temperatures as low as 25 ∘ C.…”
Section: Model Analysismentioning
confidence: 99%
“…Novel adsorption materials with higher working capacities could reduce the footprint of the system as smaller adsorption beds could produce the same amount of distillate. One challenge in material selection is the working capacity from the material's equilibrium curves that can be achieved at 40 ∘ C. Most novel materials that have been proposed for adsorption desalination showing high water capacities require regeneration temperatures well above 40 ∘ C, for example, MOF materials (90 ∘ C) 79,80 or zeolites AQSOA Z01 and Z02 (60 ∘ C and 80 ∘ C). 76,77 Ionogels show outstanding performances at regeneration temperatures as low as 25 ∘ C. Hence, ionogels would be ideal for the ADRED process.…”
Section: Limitations and Considerations For Industrial Applicationsmentioning
confidence: 99%